2013
DOI: 10.1111/ina.12019
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double‐blind crossover study of indoor air filtration and acute changes in cardiorespiratory health in a First Nations community

Abstract: Few studies have examined indoor air quality in First Nations communities and its impact on cardiorespiratory health. To address this need, we conducted a crossover study on a First Nations reserve in Manitoba, Canada, including 37 residents in 20 homes. Each home received an electrostatic air filter and a placebo filter for 1 week in random order, and lung function, blood pressure, and endothelial function measures were collected at the beginning and end of each week. Indoor air pollutants were monitored thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 30 publications
7
69
1
4
Order By: Relevance
“…indoor concentrations of PM 2.5 in a panel study of elderly especially during winter (Simoni et al, 2003) and in an indoor air filtration crossover study with young adults (Weichenthal et al, 2013). By contrast, our investigation encompassed only non-smokers without asthma, living in non-smoking homes and lung function was not associated with PM 2.5 only with PNC levels.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…indoor concentrations of PM 2.5 in a panel study of elderly especially during winter (Simoni et al, 2003) and in an indoor air filtration crossover study with young adults (Weichenthal et al, 2013). By contrast, our investigation encompassed only non-smokers without asthma, living in non-smoking homes and lung function was not associated with PM 2.5 only with PNC levels.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, two short-term intervention studies with filtration of indoor air resulting in 60-70% decrease in indoor PNC and/or PM 2.5 for 2-7 days, in areas with either traffic or wood smoke pollution, showed increased MVF in the subjects, including elderly people (Allen et al, 2011;Brauner et al, 2008a). However, a third air filtration study among young healthy subjects showed no effect on MVF (Weichenthal et al, 2013). No effect of 24-hour exposure to air from a busy street, with a PNC of around 10,000 particles/cm 3 , was found on MVF in young healthy adults (Brauner et al, 2008b).…”
Section: Discussionmentioning
confidence: 95%
“…Research efforts including both simulations and field measurements have demonstrated increased negative health effects or poor IAQ in efficient or retrofitted residences that did not sufficiently address IAQ provisions (Emmerich et al, 2005;Milner et al, 2014;Offermann, 2009;Wilson et al, 2013). Yet, other research efforts that have consistently included IAQ best practices have demonstrated improved health outcomes and generally reduced pollutant levels (Breysse et al, 2011;Jacobs, 2013;Kovesi et al, 2009;Leech et al, 2004;Noris et al, 2013a;Weichenthal et al, 2013). These mixed research findings substantiate the concerns of those who are concerned that efficiency may be implemented in residences without sufficient IAQ countermeasures.…”
Section: Additional Indoor Pollutantmentioning
confidence: 95%
“…Enhanced filtration and other particle removal systems (described collectively in this document as "filtration") have the potential to reduce PM 2.5 concentrations and exposures (Barn et al 2008;Macintosh et al 2008). Recent studies showed health benefits from filtration in homes and commercial buildings (Fisk 2013), including some that may be linked to cardiovascular disease (Lin et al 2011;Weichenthal et al 2013), and other studies that found reduction in symptoms of asthma, allergies etc. (Sublett et al 2010).…”
Section: Introductionmentioning
confidence: 99%